Bradycardia in perspective—not all reductions in heart rate need immediate intervention. Issue 1 (20th November 2014) - Mason, Keira P.; Lönnqvist, Per‐Arne; Morton, Neil
Summary According to Wikipedia, the word 'bradycardia' stems from the Greek βραδύς, bradys, 'slow', and καρδία, kardia, 'heart'. Thus, the meaning of bradycardia is slow heart rate but not necessarily too slow heart rate. If looking at top endurance athletes they may have a resting heart rate in the very low thirties without needing emergent intervention with anticholinergics, isoprenaline, epinephrine, chest compressions or the insertion of an emergency pacemaker (Figure 1). In fact, they withstand these episodes without incident, accommodating with a compensatory increase in stroke volume to preserve and maintain cardiac output. With this in mind, it is difficult for the authors to fully understand and agree with the general sentiment amongst many pediatric anesthesiologists that all isolated bradycardia portends impending doom and must be immediately treated with resuscitative measures.